IDENTIFIKASI MODEL MENTAL SISWA SMA KELAS X PADA MATERI HUKUM NEWTON TENTANG GERAK - Susanti Rahayu; Joko Purwanto (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
This study are aimed to identificate student’s mental models of Newton’s Law of Motion and its factors that possed for X grade at State Senior High School 5 Yogyakarta. This study measured up by Newton II Law. This is a descriptive research. The population of this research are students of X grade at State Senior High School 5 Yogyakarta, 243 students. This sample selected 101 students by purposive sampling technique. This study used test and non-test methods. Two tier multiple choice diagnostic test used to find coceptual understanding (step I) and identificate the student’s mental models (step II). The questionnaire used to identificate the factors that possed the student’s mental models. In addition, interview holded for confirm the student’s answers. The results found that students have three determined mental models. The students have Newtonian model with 18%, the most student used Hybrid model with 24%,Ariestotelian model with 11% and another model with 47%. Student’s mental models influenced by experiment with 10%, student even see the same case 6% and 30% is learning from physics book. There are 54% of student’s mental models influenced by another factor, such as logical resoaning ang teacher’s explanation.